Greenhouse gases emission from oil palm plantations converted from different land uses - Mat Akhir, Nurul Izzati (2016)
The environmental impacts with regard to agro-based biofuel production have been associated with the impact of greenhouse gas (GHG) emissions. This is particularly related with the release of nitrous oxide (N2O) emission which result from the plantation activities throughout the production of palm oil. Therefore, this study aims to evaluate on GHG emissions from oil palm plantations converted from different land uses. In this study, field GHG emissions during plantation stage of palm oil-based biofuel production have been evaluated in association with different age of oil palm and land conversion scenarios for oil palm plantation development. Three different sites of different land conversion prior to oil palm plantation were chosen; transformed land-use (large and small-scales) and logged-over forest. Field sampling for determination of soil Nmineralization and soil organic carbon (SOC) was undertaken at sites according to the age of palm, i.e. < 5 years (immature), 5-20 years and >21 years (mature palms). Data of N-fertilizer application was also obtained from scheduled fertilizing scheme at one site to observe the variation of nitrous oxide emissions over years. The field data were incorporated into the estimation of N2O and the resulting CO2-eq emissions as well as for estimation of carbon stock changes. Irrespective of the land conversion scenarios, the N2O emissions were found in the range of 6.47-7.78 kg N2O-N/ha resulting in 498-590 kg CO2-eq/ha. There was no apparent difference of N2O emissions between different land conversion scenarios for oil palm plantation development. However, the amount of N2O emissions were slightly higher for immature oil palms (< 5 years) compared to mature palms (> 5 years) for all types of land use conversion. The resulting CO2-eq emissions follow the same trend as for the N2O emission, i.e. emission is slightly higher during early stage of oil palm development. The N2O emission constituted the largest portion of GHG emissions among the major inputs of GHGs during the plantation stage of oil palm development, whereby the contribution of N from organic matter decomposition was found significant. On the other hand, the conversion of tropical forest into oil palm plantation has resulted in relatively higher GHG emissions (i.e. 4 times higher and carbon stock reduction by >50%) compared to transformed land use for oil palm development. The conversion from previously rubber plantation into oil palm plantation would increase the carbon savings (19% in increase) thus sustaining the environmental benefits from the palm oil-based biofuel production. Therefore, the results from this study have highlighted the contribution of GHG emissions from oil palm plantation of different stages and with associated land conversion scenarios. The findings would be of useful contribution to site-specific cases of GHG emissions with regard to oil palm plantation development for biofuel production.